Early onset Cockayne's syndrome: case reports with neuropathological and fibroblast studies. Issue 3 (March 1989) - Patton, M A; Giannelli, F; Francis, A J; Baraitser, M; Harding, B; Williams, A J
Abstract : Two patients with early onset Cockayne's syndrome are presented. In each case there was a striking failure of growth and developmental deterioration around six months of age. It has been suggested that early onset Cockayne's syndrome is a syndrome distinct from Cockayne's syndrome, but when the first patient died aged two years 10 months, examination of the brain showed a leucodystrohy with 'tigroid' demyelination similar to that reported in later onset cases of Cockayne's syndrome. Studies of the effects of UV irradiation on cultured fibroblasts from patients showed similar levels of inhibition of RNA synthesis to those seen in a control with Cockayne's syndrome. This evidence suggests it is appropriate to classify early onset Cockayne's syndrome with Cockayne's syndrome. Since there is a phenotypic overlap between early onset Cockayne's syndrome and COFS syndrome, they may both be classified within the same diagnostic group, but as yet no cellular studies with UV irradiation have been performed in COFS syndrome.